S77 The idiopathic pulmonary fibrosis patients reported outcome measure (IPF-PROM) is reliable and valid for use in populations with IPF. (December 2018) - Russell, AM; Wickremasinghe, M; Renzoni, E; Adamali, H; Borril, Z; Fletcher, S; Maher, TM; Ng Man Kwong, G; Saketkoo, LA; Fleming, S; Cullinan, P
Abstract : Introduction: The IPF-PROM has been developed using rigorous patient-centred and psychometric methods. Triangulated qualitative approaches generated items that were relevant and specific to IPF populations. The 12-item questionnaire has 4-domains which measure the physical and psychological experiences of breathlessness, emotional well-being and energy levels. Methods: A new population of eight-five patients with IPF recruited from five NHS centres participated in the 12 month IPF-PROM validation study; serial questionnaires were completed 3 monthly. Mean age 75.3±8 years. Baseline FVC 74.18% predicted (±16.14); DLCO 39.21% predicted (±14.43) and BMI 26.98 (±4.73). Content and face validity of the IPF-PROM were qualitatively assessed. Construct Validity was confirmed by principle components analysis (PCA); concurrent validity was assessed by correlations with FVC, SGRQ and EQ-5D-L VAS using Pearson's correlation coefficient (r) and with MRC dyspnoea grade and EQ5D domains using Spearman's coefficient (R 2 ). Results: The IPF-PROM has very good test-retest reliability. The median timeframe between time-point one and two was 19 days. The intra-class correlation coefficients (ICC) were all >0.8. Domain-1 0.835 (p=0.209); Domain-2 0.895 (p=0.150); Domian-3 0.813 (p=0.786) Domain-4 0.863 (p=0.761) Total 9.2 (p 0.784) Internal Reliability was further tested using Cronbach's alpha (α). Domain-1 α=0.874; Domain-2 α=0.870; Domain-3 α=0.900; Domain-4 α=0.849 and total α=0.920. Sixty patients completed 12 months of the study; fifteen patients (17%) died and ten patients (11%) discontinued their involvement for reasons unknown. PCA confirmed a two factor model with eigen values>1.0 accounting for 75% of variance. All 12-items had a factor loading >0.5. The IPF-PROM correlates strongly with MRC; SGRQ; EQ-5D-L and moderately significantly with FVC. See table 1. Discussion: The IPF PROM is reliable and valid for use. Longitudinal validation studies are challenging due to the uncertain trajectory and mortality associated with IPF. Additional studies are ongoing to affirm the responsiveness of the IPF-PROM. The IPF-PROM is available in other European languages.